Rancang Bangun Aplikasi Photo Booth Interaktif Berbasis Web dengan Fitur Layout, Filter, dan Frame Menggunakan Pemrograman Berorientasi Objek - Putri Dwi Manggali; Ahmad Tabrani (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
This research aims to design and build a web-based interactive photo booth application with layout, filter, and frame features using object-oriented programming concepts. The application was developed as an alternative solution to digital photo booths that can be accessed directly through a web browser without the need for additional installation. The system development method used is the Waterfall method which includes the stages of needs analysis, system design, implementation, and testing. The technology used in application development includes HTML, CSS, JavaScript, and the use of Web APIs to access the device's camera and process images in real-time. The results of the study show that this web-based photo booth application is able to run well on modern browsers, providing photo capture features, layout settings, filter application, and interactive frame addition. The implementation of object-oriented programming results in a more modular code structure, is easy to understand, and facilitates the development and maintenance of future systems. Thus, the developed application can become a practical, flexible, and easy-to-use digital photography medium.